Assesinng Sustainable Development Goal 11 in South African Context - Vyas-Doorgapersad, Shikha (Journal of Economic Development, Environment and People, 2023)
South Africa underwent apartheid, a system of racial segregation, during which the country's governance agendas did not offer too much emphasis on environmental issues. The policies implemented during that time were lacking the environment-inclusiveness, and thus regrettably remained unsuccessful in promoting sustainable development. This article aims to review the current state of SDG 11, which focuses on sustainable cities and communities, in South African context. This research is a qualitative analysis of secondary data obtained through reviewing literature. The data was analyzed using conceptual analysis. The literature review shows that the democratic governance in a post-apartheid era implemented some policies that now regulate various aspects of SDG 11 in the country-specific context. Some of the significant ones are the Housing Act (No. 107 of 1997); Water Services Act (No. 108 of 1997); National Environmental Management: Waste Act (No. 59 of 2008); Municipal Systems Act (No. 32 of 2000); Breaking New Ground, 2004; and the National Housing Code, 2009. However, despite these legislative frameworks, there are challenges that still hamper the effective achievement of SDG 11. The findings therefore explore these challenges that include insufficient skills, inadequate funding, and inadequate training to develop technical competence, among others. The study provides recommendations for addressing these issues and improving the situation.